Assessment of Equipment Handling Practices in the Hospitality Industry: A Case Study of Kathmandu’s Key Departments - Shrestha, Jenisha; Chaudhary, Rajeshwer Prasad (International Journal of Atharva, 2024)
This study investigates equipment handling practices within the hospitality industry in Kathmandu, focusing on the frequency of use, types of equipment handled, training provided, and safety measures observed. A descriptive research design was employed, utilizing a quantitative survey approach that targeted 125 participants across three key departments: food production, food and beverage service, and housekeeping. Random sampling techniques were applied to conduct in-depth inspections, evaluate staff training, and assess the documentation and maintenance routines. The findings reveal that a significant portion of staff handles equipment daily, with food production equipment being the most commonly used. While training on equipment handling is regularly provided, issues such as the lack of written guidelines, limited access to personal protective equipment (PPE), and infrequent maintenance checks were identified as critical concerns. Additionally, safety protocols, particularly for heavy equipment, and the clarity of operational instructions were found to be inadequate in some cases. The study underscores the importance of consistent training, proper documentation, and the implementation of safety protocols to enhance equipment handling practices in the hospitality sector.